(untitled) (Training and Practice : Journal of Educational Sciences, 2014)
The goal of this research is to reveal the situation of general configurations of Hungarian non-vocational adult education, both from the sides of the institutions as well as the programmes. This research has several components, while analysing both the Hungarian and the international special literature, the re-analysis of the existing data bases was carried out and interviews were made with institution directors and experts. Our study presents partial results of this multi-component research. Principally it concentrates on analysing data of our own data base made from registrations. First of all, we analyse supply, what the potential institutional and programme supply for adults is, and what differences and deviations in regions with various social-economical background can be found.